Dispersive Liquid-Liquid Microextraction Combined with Electrothermal Atomic Absorption Spectrometry for Determination of Trace Lead in Drinking Water Samples - Liu, Y.L.; Wu, X.Y.; Xiang, G.Q.; He, L.J.; Jiang, X.M.; Zhang, H.X.; Chen, F.P. (Asian Journal of Chemistry, 2011)
A new method of dispersive liquid-liquid microextraction combined with electrothermal atomic absorption spectrometry was proposed for the determination of trace lead using sodium diethyldithiocarbamate as chelating reagent. Several factors influencing the microextraction efficiency of lead and the subsequent determinations, such as extraction and disperser solvent type and their volume, pH, concentration of diethyldithiocarbamate and extraction time were investigated. Under the optimum conditions, the detection limit of the proposed method was 0.006 ng mL-1 for lead and the relative standard deviation was 3.5 % (c = 0.1 ng mL-1, n = 7). The proposed method was successfully applied to the determination of trace lead in mineral water samples and the recoveries for the spiked samples was in the range of 96-108 %.